Domesticating dating apps: Non-single Chinese gay men's dating app use and negotiations of relational boundaries. (April 2021) - Wu, Shangwei
Dating app use is prevalent among non-single Chinese gay men. Applying domestication theory, this study explores how dating apps can be accepted in gay romantic relationships. The author argues that the domestication of technological artifacts unfolds on four dimensions: the practical, the symbolic, the cognitive, and the relational . Findings show that dating apps serve a dual role: a pool of sexual or romantic alternatives and a channel to the gay community. Although the former constitutes a threat to monogamy, the latter leaves room for a couple's negotiation for acceptable but restricted uses. This negotiation is in tandem with the negotiation of relational boundaries, which leads to either the reinforcement of monogamy or the embrace of non-monogamy. Meanwhile, one can perceive dating apps to be as unremarkable as other social media platforms. This is achieved through a cognitive process where gay men learn to debunk the arbitrary association between dating apps and infidelity. Monogamous or not, they put faith in user agency, not perceiving dating apps as a real threat to romantic relationships.